Causes of dog mortality in Paraíba/Brazil: Use of DATASIMA for data diagnosis and mapping - Eduardo S.S. Sousa; Maria E.S. Sousa; Moisés D.C.A. Pereira; Ricardo A.M. Negreiros; Arthur W.L. Brasil; Inácio J. Clementino; Sérgio S. Azevedo; Ricardo B. Lucena (Pesquisa Veterinária Brasileira)
ABSTRACT: Analyzing the causes of death in dogs is fundamental for controlling and preventing diseases, thereby promoting greater longevity and quality of life. However, the current literature lacks standardization and uniformity in the diagnostic description, forms, and instruments for collecting data and maintaining dog obituary records. Using data from the Data Platform of the Animal Mortality Information System (DATASIMA), which uses the Declaration of Animal Death and the International Classification of Diseases (ICD-10), the classification of the causes of death of dogs attended by veterinary doctors was conducted at the “Universidade Federal da Paraíba”, from January to December 2022. The causes of death were stratified, promoting their geo-referencing and the characterization of the epidemiological profile of the dogs. A total of 264 cadavers were analyzed, and the most prevalent groups of diseases causing death were pathophysiological disorders (37.87%, n=100), infectious and parasitic diseases (28.4%, n=75), neoplasms (21.59%, n=57), and external causes (12.12%, n=32). The causes of death were categorized according to sex and age range, showing a higher prevalence of pathophysiological disorders and infectious diseases in adults, neoplasms in elderly dogs, and infections and parasitic diseases and pathophysiological disorders in offspring. The findings of this study demonstrate the feasibility of using DATASIMA for the mapping and standardization of data on the causes of animal death, allowing for strategies for intervention in public health, the prevention of zoonoses, the reduction of garbage codes, better and more efficient communication between veterinary doctors, and the possibility of using ICD-10 to classify the causes of animal death.